2020
DOI: 10.1111/acps.13169
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the cognitive underpinnings of voice‐hearing by comparing never, past and current voice‐hearers

Abstract: Objective The current study aimed to compare specific cognitive profiles corresponding to auditory verbal hallucinations (AVH) status and elucidate which pattern of cognitive deficits may predict voice‐hearing status. Method Clinical participants with schizophrenia spectrum disorders were partitioned into: (i) current voice‐hearers (n = 46), (ii) past voice‐hearers (n = 37) and (iii) never voice‐hearers (n = 40), and compared with 319 non‐clinical controls. Cognitive assessment employed the MATRICS Consensus C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Moreover, we further found that AVH patients had more severe cognitive impairment in visual learning and verbal learning compared to non-AVH patients. This is partially consistent with previous studies which suggested that compared to never voice-hearers, current and past voice-hearers are more likely to encounter difficulties in integrating new information on the visual learning domain, but not significant more impaired in verbal learning (38,39). However, other studies have exhibited that poorer performance on verbal working memory was identified as the independently predictor of the severity of AVH in firstepisode schizophrenia patients (7).…”
Section: Cognitive Dysfunction In Schizophrenia Patients With Avhsupporting
confidence: 92%
“…Moreover, we further found that AVH patients had more severe cognitive impairment in visual learning and verbal learning compared to non-AVH patients. This is partially consistent with previous studies which suggested that compared to never voice-hearers, current and past voice-hearers are more likely to encounter difficulties in integrating new information on the visual learning domain, but not significant more impaired in verbal learning (38,39). However, other studies have exhibited that poorer performance on verbal working memory was identified as the independently predictor of the severity of AVH in firstepisode schizophrenia patients (7).…”
Section: Cognitive Dysfunction In Schizophrenia Patients With Avhsupporting
confidence: 92%
“…Although broad summaries of executive function and AHs are yet to be provided, our observation of limited significant findings were mostly consistent with recent empirical conclusions (e.g. Toh et al, 2020 ). Given that a critical portion of literature was omitted from this review due to a lack of methodological specificity to AHs, the absence of substantial evidence noted in respect to the above cognitive sub-domains does not necessarily disconfirm the relevance of these processes, but rather highlights the need for further methodological rigour in validating such inferences.…”
Section: Discussionsupporting
confidence: 91%
“…However, a notable portion of non-significant findings have also been reported (e.g. Brébion et al, 2008;Johns et al, 2001;McKay et al, 2000;McLachlan et al, 2013;Pinheiro et al, 2016;Rocca et al, 2006;Rossell et al, 2001;Schnakenberg Martin et al, 2018;Toh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, both intrusions and false recognitions were reliably associated with AVH, and these mistakes did not seem dependent on the semantic structure of words (p. 7). Another recent study conducted by Toh et al (2020) employs a battery of tasks to assess the degree of EF disruption in three subgroups diagnosed with schizophrenia: current voice-hearers, past voice-hearers, and never voice-hearers. Notably, current voice-hearers were found to be more impaired in the inhibition and visual learning domain (i.e., visual organization tasks requiring elements of planning), both with respect to controls and clinical subjects who had not recently experienced AVH.…”
Section: Executive Functions and Inner Speech In Sz-avhmentioning
confidence: 99%